Dry matter intake decreases shortly after initiation of feeding Zilmax during the summer - Christopher D. Reinhardt; Christopher I. Vahl; Brandon E. Depenbusch (Kansas Agricultural Experiment Station Research Reports, 2014)
Tenderness, juiciness, and flavor play important roles in a satisfactory beef eating experience. All three factors can be affected by management decisions made by producers during the production of beef. Beef producers currently use a multitude of production programs that utilize feed additives such as Rumensin or Tylan (Elanco Animal Health, Greenfield, IN), and growth promotants such as implants and Optaflexx (Elanco Animal Health). Rumensin and Tylan are fed in combination to improve feedlot performance, whereas growth promotants improve feed efficiency, average daily gain, hot carcass weight, and yield grades of carcasses. Although the use of feed additives and growth promotants improves production efficiency, they can affect meat characteristics such as tenderness and water-holding capacity. The Alltech PN Beef Program (Alltech Inc., Nicholasville, KY) consists of two products that are designed to replace components of the conventional feedlot diet. The PN Beef Receiver is intended to be fed during the step-up period of feeding, whereas PN Beef Finisher is intended to be fed during the remainder of finishing period. Because both products are new feed alternatives, the objective of this study was to compare the fresh cooked meat quality of the Alltech PN Beef Program to a conventional feedlot diet when both diets are combined with or without growth promotants.
Keywords: Cattlemen' s Day; 2014; Kansas Agricultural Experiment Station contribution; no. 14-262-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1101; Beef Cattle Research; 2014 is known as Cattlemen' s Day; Feedlot cattle; Zilmax; Dry matter intake (DMI); Beef